Proximal and distal predictors of self-regulatory change in children aged 4 to 7 years - Williams, Kate E.; Howard, Steven J. (My University, 2020)
Growth in early self-regulation skills has been linked to positive health, wellbeing, and achievement trajectories across the lifespan. While individual studies have documented specific influences on self-regulation competencies in early childhood, few have modelled a comprehensive range of predictors of self-regulation change across health, development, and environment simultaneously. This study aimed to examine the concurrent associations among a range of proximal and distal influences on change in children's self-regulation skills over 2 years from age 4-5 years. Data from the Longitudinal Study of Australian Children (N = 4983) were used in a structural equation model, predicting a multi-source composite measure of self-regulation at each of 4-5 years and 6-7 years. By controlling for earlier self-regulation and covariates, the model examined the relative contributions of a comprehensive range of variables to self-regulation change including health, development, educational, home environment, time-use, and neighbourhood characteristics. The significant predictors of children's self-regulation growth across 4 to 7 years were fewer behavioural sleep problems, higher gross motor and pre-academic skills, lower levels of maternal and paternal angry parenting, and lower levels of financial hardship. There were also marginal effects for high-quality home learning environments and child-educator relationships. Findings suggest that if we are to successfully foster children's self-regulation skills, interventionists would do well to operate not only on children's current capacities but also key aspects of their surrounding context.
BMC Pediatrics
Keywords: Childhood and child development